Luminal Bacteria Recruit CD103+ Dendritic Cells into the Intestinal Epithelium to Sample Bacterial Antigens for Presentation - Farache, Julia; Koren, Idan; Milo, Idan; Gurevich, Irina; Kim, Ki-Wook; Zigmond, Ehud; Furtado, Glaucia C.; Lira, Sergio A.; Shakhar, Guy (Immunity (Cambridge, Mass.), 2013)
CD103+ dendritic cells (DCs) carry bacteria from the small intestine and can present antigens to T cells. Yet they have not been recorded sampling luminal bacteria or presenting bacterial antigens in mesentery lymph nodes. We used 2-photon microscopy in live Cx3cr1+/gfp ×Cd11c-YFP mice to study these processes. At steady state, sparse CD103+ DCs occupied the epithelium. They patrolled among enterocytes while extending dendrites toward the lumen, likely using tight-junction proteins to penetrate the epithelium. Challenge with Salmonella triggered chemokine- and toll-like receptor (TLR)-dependent recruitment of additional DCs from the lamina propria (LP). The DCs efficiently phagocytosed the bacteria using intraepithelial dendrites. Noninvasive bacteria were similarly sampled. In contrast, CD103+ DCs sampled soluble luminal antigen inefficiently. In mice harboring CD103+ DCs, antigen-specific CD8 T cells were subsequently activated in MLNs. Intestinal CD103+ DCs are therefore equipped with unique mechanisms to independently complete the processes of uptake, transportation, and presentation of bacterial antigens. ► CD103+ DCs patrol the epithelium of the small intestine ► Salmonella infection recruits more DCs in a TLR and chemokine-dependent manner ► The DCs efficiently phagocytose salmonella using intraepithelial dendrites ► Soluble luminal antigens are sampled more efficiently by CX3CR1+ macrophages